Prevalence and Predictors of Premature Coronary Heart Disease Among Asians in the United States: A National Health Interview Survey Study - Kianoush, Sina; Rifai, Mahmoud Al; Jain, Vardhmaan; Samad, Zainab; Rana, Jamal; Dodani, Sunita; Jia, Xiaoming; Lee, Michelle; Khan, Safi U.; Gupta, Kartik; Lavie, Carl J; Wong, Sally S.; et al. (Current problems in cardiology, 2023)
Identifying Asian subgroups with higher risk of premature coronary heart disease (CHD) can help implement targeted strategies to prevent future CHD events. We conducted this National Health Interview Survey study from 2006 to 2015 among participants with history of CHD to compare the risk of premature CHD (<65 for women and <55 years old for men) across Whites, Chinese, Asian Indians, Filipinos, and “other Asians” (Japanese, Korean, and Vietnamese individuals) using univariate and multi-variable logistic regression models. A total of 17,266 participants with history of CHD (mean age, 66.0 ± 0.2; 39% women) were included. Risk of premature CHD was higher among Asian Indians (OR = 1.77, 1.05-2.97) and “other Asians” (OR = 1.68, 1.17-2.42) than Whites adults. Compared with Chinese, the risk of premature CHD was significantly higher for Asian Indians in the unadjusted models (OR = 2.72, 1.19-6.3). “Other Asians” exhibited significantly higher risk in crude (OR = 2.88, 1.32-6.27) and adjusted models (aOR = 2.29, 1.01-5.18). Among younger adults (<50 years) with CHD, Asian Indian adults (aOR = 2.43, 1.26-4.70) and other Asian adults (aOR = 1.86, 1.14-3.02) showed higher odds of premature CHD compared with White adults. The risk of premature CHD varies across Asian populations. More studies with an adequate sampling of Asian subgroups are needed to identify the risk and determinants of premature CHD.